Building Cooperation between the BRICS and Leading Industrialized States1. (17th October 2013) - Luckhurst, Jonathan
<x xml:space="preserve">Abstract</x> This article examines relations between the BRICS and leading industrialized states. It starts by analyzing the former's mutual relations, focusing on how the ideational construct presented by Jim O'Neill in his "BRIC hypothesis" became formalized as a leader‐level diplomatic group at a summit in Yekaterinburg, Russia, in 2009. I evaluate how the BRICS have influenced international issues and whether "cooperation" or "conflict" characterizes their relations with key industrialized states, concluding that there has been greater multilateral cooperation since 2008, especially through international forums such as the G20. The BRICS partnership is one of unequals, significant for international economic relations primarily due to China. This has had important consequences as the Chinese government has prioritized economic cooperation with leading industrialized states. Influential countries can continue to benefit by enhancing multilateral ties in what are often nonzero–sum situations.